Experimentação no ensino de física: um estudo escolas estaduais na região de São José dos Campos - Duarte, Cristiano [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work presents the results of a study on the use of experimentation in physics teaching, presenting a survey on the use of this strategy in public high schools in the region of São José dos Campos. Data collection was carried out in schools by means of questionnaires prepared for physics teachers and students from three grades of high school. Data were obtained in eighteen schools distributed in the city of São José dos Campos (two in the central region, in the west, three on the east side, seven in the north and five in the south), a school in the district of Sao Francisco Xavier and a school in the town of Monteiro Lobato. Thus, data from 20 schools, 610 students and 20 teachers were analyzed. Among the main results, we highlight that over 80% of the students said that there is no physics lab at the school where they study, and less than 1% declares that uses laboratory weekly. We note that there is a laboratory in 25% of the schools in the northern region and 10% or less of the other schools. According to the students the proposition of the experimental activities by teachers is rare - only three schools in East Side the options sometimes and always exceeded the number of responses experimental activities are never proposed. We had 60% of the teachers who reported using the curriculum of the state of São Paulo to propose activities to students, and half of the teachers said they did not have classes experimental physics classes in initial training or had them in sufficient quantity to support the use of this feature in practice

Este trabalho apresenta os resultados de um estudo sobre o uso da experimentação no ensino de Física, apresentando um levantamento sobre o uso dessa estratégia em escolas públicas de ensino médio na região de São José dos Campos. A coleta de dados nas escolas foi realizada por meio de questionários elaborados para os professores de física e para alunos das três séries do Ensino Médio. Obtivemos dados em dezoito escolas distribuídas na cidade de São José dos Campos (sendo duas na região central, uma na zona oeste, três na zona leste, sete na zona norte e cinco na zona sul), uma escola no distrito de São Francisco Xavier e uma escola na cidade de Monteiro Lobato. Dessa forma, foram analisados dados de 20 escolas, 610 alunos e 20 professores. Dentre os principais resultados obtidos destacamos que mais de 80% dos alunos disseram que não há laboratório de Física na escola onde estuda e menos de 1% declara que utiliza laboratório semanalmente. Constatamos que existe laboratório em 25% das escolas da zona norte e em 10% ou menos nas demais escolas. De acordo com os alunos a proposição de atividades experimentais pelos professores é pouco frequente -apenas nas três escolas da zona leste as opções às vezes e sempre superaram o número de respostas nunca são propostas atividades experimentais. Tivemos 60% dos professores que declararam usar o currículo do estado de São Paulo para propor atividades aos alunos, e metade dos professores afirmaram que não tiveram aulas de física experimental na formação
Keywords: Física - Estudo e ensino; Aprendizagem por atividades; Escolas públicas; Physics Study and teaching